Structural and optical properties of mixed phase WO3 – ZnWO4 films synthesized from thermally oxidized metallic Zn–W films - Jovanovski, Stefan; Popović, Maja; Novaković, Mirjana; Ristova, Mimoza (Elsevier BV, 2026)
Tungsten-bearing compounds have attracted significant interest in recent years, especially in thin films or nano powder form, due to their photocatalytic activity stemming from their wide band gap semiconductor properties. This study presents the synthesis of mixed phase WO3–ZnWO4 films synthesized by thermal oxidation of co-sputtered metallic Zn–W films. From XRD analysis it appeared that annealing at 600 °C leads to the formation of the monoclinic Zn-tungstate phase within the WO3 matrix with crystallite size about 50 nm for both phases. The XPS analysis of the O1s peak showed mixed phase compound of WO3 matrix with about 13 at.% of ZnWO4. Raman and infrared spectroscopy further characterize the structural features, revealing the WO6 octahedral unit as main building block in the structure. The optical band gap of the annealed film was found to be 3.34 eV, indicating a wide gap semiconductor. The films displayed a UV induced Photoluminescence with broad PL spectra with emission maximum at about 2.48 eV. The study demonstrates that co-sputtering and annealing at 600 °C approach is effective for synthesizing of tungstate phase ZnWO4 within WO3 matrix.
NA
Keywords: WO3; ZnWO4; thin films; RF/DC sputtering; XPS; XRD